ANTIOXIDANT ACTIVITY AND TOTAL PHENOLIC CONTENT IN RIPE AND UNRIPE POMEGRANATE (PUNICA GRANATUM L.) FRUIT JUICE - AMJAD, MUHAMMAD; ANWER, ZOBIA (International Journal of Current Pharmaceutical Research, 2021)
Objective: P. granatum L. is famous for antioxidant activity and utilized as a nourishing foodstuff. This work aimed to recognize the antioxidant activity and TPC in extracts of ripe and unripe fruit juice. Methods: Competency of the solvents (water, methanol, acetone, chloroform, ethanol) were evaluated by analyzing extracts of ripe and unripe P. granatum L. fruit juice for TPC and DPPH* scavenging assay. FTC method measured the level of peroxides. Results: In TPC extraction, the water solvent showed greater potential in both ripe (10.5±2.1) and unripe fruit juice (4.1±0.3) amongst all other solvents. Ethanol and water solvent showed the highest value of DPPH* scavenging activity (96%±6.81 and 72%±3.50 respectively) in ripe and unripe fruit juice. According to absorbance of DPPH radicals, the water solvent showed the highest antioxidant potential in ripe fruit juice (86%±6.78) like chloroform solvent in unripe fruit juice (14%±0.03). Unripe fruit juice showed lowest level of absorbance of DPPH radicals and highest antioxidant potential amid all solvents. In FTC method, unripe fruit juice showed the highest antioxidant activity and low amount of peroxides for consecutively seven days. Conclusion: Ripe fruit juice showed the highest TPC and unripe fruit juice showed the maximum value of antioxidant potential. P. granatum L. provides an excellent supply of antioxidant activity and used in pharmaceutical and food industry.